O-GlcNAc modification regulates autophagy and apoptosis in endometriosis - Xiaohan Jin; Yali Feng; Lei Xu; Jing Li; Linping Fan; Jinge Li; Runyuan Liu; Qing Yang; Ying Kong; Yuhong Shang (Functional & Integrative Genomics, 2026)

Exosomes derived from first-trimester human decidual mesenchymal stem cell - Yuxian Wang; Linping Jin; Miaojie Fang; Xujia Huang; Jian Xu (Tissue and Cell, 2026)

Decoding the partitioning behavior of poly- and perfluoroalkyl substances: Insights from human liver and blood biomonitoring with machine learning - Linping Cao; Yishu Zheng; Wenfei Yu; Jiaqi Shao; Yu Fu; Yating Liu; Weichen Zhang; Jiamian Fang; Yuanchen Chen; Hangbiao Jin (Environmental Pollution, 2026)

Comprehensive analysis of intracellular electron transfer and microbial succession in response to florfenicol in mixotrophic denitrification systems - Shaofei Yang; Yunzhu Ding; Linping Tang; Chunji Jin; Yangguo Zhao; Liang Guo (Environmental Research, 2025)

Synergistic mechanisms of compound thermophilic bacteria on waste sludge hydrolysis and reduction: Extracellular polymers degradation, enzyme activity and microbial community changes - Meiping Sui; Ke Miao; Linping Tang; Jianwei Zhao; Chunji Jin; Yangguo Zhao; Liang Guo (Science of The Total Environment, 2025)

Transplacental transfer of p-phenylenediamine antioxidants: Insights from human gestational exposure and an optimized BeWo cell monolayer model - Junxu Li; Fangfang Ren; Linping Cao; Hangbiao Jin; Yang Li (Journal of Hazardous Materials, 2025)

A refined two-stage microalgal phosphorus uptake model incorporating enzymatic delay dynamics improves predictive accuracy - Jinfeng Han; Wei Cao; Linping Tang; Chunji Jin; Yangguo Zhao; Yi Wang; Liang Guo (Chemical Engineering Journal, 2025)

Integrated physiological and proteomic analyses reveal differential responses of microalgae to inorganic phosphate forms in wastewater - Jinfeng Han; Wei Cao; Linping Tang; Chunji Jin; Yangguo Zhao; Yi Wang; Liang Guo (Journal of Environmental Chemical Engineering, 2025)

Optimization of Phaeodactylum tricornutum cultivation for enhancing mariculture wastewater treatment and high value product recovery using Box–Behnken design - Feng You; Yiwei Fan; Linping Tang; Xiangrong Liu; Chunji Jin; Yangguo Zhao; Yi Wang; Liang Guo (Process Safety and Environmental Protection, 2025)

POD-like nanozyme constructed from perspective of charge transfer engineering for biosensing of magnetic separation treated Listeria monocytogenes - Weiqiang Li; Xiaoyun Xu; Yang Song; Linping Fan; Jin Huang; Luyu Yang; Yang Liu; Hengyi Xu (Food Chemistry, 2025)

6:2 Cl-PFESA, a proposed safe alternative for PFOS, diminishes the gemcitabine effectiveness in the treatment of pancreatic cancer - Jiawei Hong; Keyi Du; Weichen Zhang; Junran Chen; Hangbiao Jin; Yuanchen Chen; Yifan Jiang; Hanxi Yu; Xiaoyu Weng; Shusen Zheng; Jun Yu; Linping Cao (Journal of Hazardous Materials, 2024)

Enhanced NMDA receptor pathway and glutamate transmission in the hippocampal dentate gyrus mediate the spatial learning and memory impairment of obese rats - Dingding Lv; Bin Xiao; Huaying Liu; Linping Wang; Yingshun Li; Yin Hua Zhang; Qinghua Jin (Pflügers Archiv - European Journal of Physiology, 2024)
Obesity has been linked with the impairment of spatial memory and synaptic plasticity but the molecular mechanisms remained unidentified. Since glutamatergic transmission and NMDA receptor neural pathways in hippocampal dentate gyrus (DG) are essential in the learning and memory, we aimed to investigate glutamate (Glu) and NMDA receptor signaling of DG in spatial learning and memory in diet-induced obesity (DIO) rats. Spatial learning and memory were assessed via Morris water maze (MWM) test on control (Ctr) and DIO rats. Extracellular concentration of Glu in the DG was determined using in vivo microdialysis and HPLC. The protein expressions of NMDA receptor subunit 2B (NR2B), brain-derived neurotrophic factor (BDNF), the activation of calcium/calmodulin-dependent kinase II (CaMKII) and cAMP-response-element-binding protein (CREB) in the DG were observed by western blot. Spatial learning and memory were impaired in DIO rats compared to those of Ctr. NR2B expression was increased, while BDNF expression and CaMKII and CREB activation were decreased in DG of DIO rats. Extracellular concentration of Glu was increased in Ctr on the 3rd and 4th days of the MWM test, but significant further increment was observed in DIO rats. Microinjection of an NMDA antagonist (MK-801) into the DG reversed spatial learning and memory impairment. Such effects were accompanied by greater BDNF expression and CaMKII/CREB activation in the DG of DIO rats. In conclusion, the enhancement of Glu-NMDA receptor transmission in the hippocampal DG contributes to the impairment of spatial learning and memory in DIO rats, maybe via the modulation of CaMKII-CREB-BDNF signaling pathway.

Environment relevant exposure of perfluorooctanoic acid accelerates the growth of hepatocellular carcinoma cells through mammalian target of rapamycin (mTOR) signal pathway - Jiawei Hong; Xiaoyan Wang; Hangbiao Jin; Yuanchen Chen; Yifan Jiang; Keyi Du; Diyu Chen; Shusen Zheng; Linping Cao (Environmental Pollution, 2024)

First evidence of neonicotinoid insecticides in human bile and associated hepatotoxicity risk - Yuanchen Chen; Wenfei Yu; Li Zhang; Linping Cao; Jun Ling; Kaizhen Liao; Guofeng Shen; Wei Du; Kangjie Chen; Meirong Zhao; Jian Wu; Hangbiao Jin (Journal of Hazardous Materials, 2023)